Investigação dos efeitos de uma formação continuada de professores de Língua Portuguesa no tratamento de desvios ortográficos de alunos do 6º ano - Almeida, Jamille Adaça Gonçalves Martins (2020)
The proficient command of the writing system holds a high level of power within society. However, teaching spelling is still a major challenge for teachers. In view of this, this research sought to investigate the difficulties that Middle School Portuguese Language teachers go through when teaching spelling, in order to propose a continuing education action that meets the real needs of teachers in the classroom. The methodological design of this action research consists of a proposal for continuing education, with both a productive and reflective nature, which was divided into the following stages: data collection (survey) and theoretical modules with teachers; pre-test, intervention and post-test activities with the students of these teachers; and an assessment of the continuing education action. Cagliari (1995, 1999 and 2002), Faraco (2003), Morais (2010) and Roberto (2016) were the main references. The results reveal a decrease of the most frequent spelling mistakes of the students, leading us to the conclude that the continuing education action based on theories, which address the reflective teaching of spelling, promotes a change in the teaching of orthography by participant teachers who started to stimulate their students to develop the necessary skills for effective learning.